THE BIBLE'S VIEWPOINT (American Journal of Pedagogical and Educational Research, 2023)
The article included the life span of women of the Dynasty, especially the queens, some of their political and social activity, and the development of diplomatic relations based on historical sources, the conclusions are explained.